The Overall Equipment Effectiveness Improvement of the Water Filtration Systems in the Large Water Treatment Plant by Total Productive Maintenance Evaluation: A Case Study of the Water Treatment Plant - Pussawiro, Sirawit; Vorarat, Suparatchai (RMUTP Research Journal Sciences and Technology, 2022)
This research objective is to improve the overall equipment effectiveness of the water filtration systems in the case study of the Water Treatment Plant, which divides the water production into 4 production lines. The water filtration system has an electric actuator and gear, is the main machine in the water filtration system. An electric actuator and gear have more machine breakdowns. That makes the water filtration system is the bottleneck of the water production process. This research study is divided into two steps: the first step is the presentation of the equation and the steps to measure the Overall Equipment Effectiveness of the water filtration system. The equation used data from the computer maintenance management system to analysis on mean time between failure data (MTBF), mean time to repair data (MTTR) and water production process data. The results can be improved the overall equipment effectiveness of the water filtration system increased to 0.11%, 0.68%, 0.44% and 2.44%, respectively in each production process line. And increased Quantity of Filtration Water increased to 328,500 m3/year, 1,168,000 m3/year, 1,022,000 m3/year and 3,832,500 m3/year, respectively in each production process line. In this research used the pillar of focus improvement. By adding a protection system to prevent machine breakdown, because of the most of the problems are found that the protection system malfunctions. This is the most problem in the 4th And then used engineering knowledge to improve water production and the success factor are required a human resources of all parties to cooperate, brainstorm and analyze the causes of various losses in order to eliminate them.